Regulatory T cells are required for normal and activin‐promoted wound repair in mice. Issue 6 (12th March 2018) - Haertel, Eric; Joshi, Natasha; Hiebert, Paul; Kopf, Manfred; Werner, Sabine
Abstract: Healing of skin wounds is orchestrated by various types of immune cells, but little is known about the role of FoxP3 + regulatory T cells (Tregs) in this process. Here, we determined if Tregs are important for wound healing in normal mice and if they contribute to the accelerated healing of mice overexpressing the growth and differentiation factor activin. Diphtheria toxin induced Treg depletion prior to injury caused impaired healing characterized by delayed reepithelialization, reduced wound contraction, and impaired vessel maturation. The accelerated wound repair of activin‐transgenic mice was also abrogated. Mechanistically, we found a strong increase in IL‐4 levels combined with overrepresentation of T‐bet + and GATA‐3 + αβ T cells in Treg‐depleted 7‐day wounds. In addition, numbers of IFN‐γ‐ or IL‐17A‐producing CD4 + and CD4 − T cells were elevated. These results demonstrate that Treg depletion in wounds facilitates the expansion of an αβ T‐cell population with features of Th1 and Th2 cells, and suggest that concomitant changes in the cytokine milieu disturb the healing process. Abstract : Using mice that allow diphtheria toxin‐induced depletion of regulatory T cells (Tregs), we demonstrate an important role of Tregs in wound repair. In the absence of Tregs, αβ T cells accumulate in the wound and produce proinflammatory cytokines, thereby inhibiting reepithelialization, contraction of wounds, and blood vessel maturation.